Impact of roof shape on air pressure, wind flow and indoor temperature of residential buildings. Issue 2 (2nd April 2016) - Mahdavinejad, Mohammadjavad; Javanroodi, Kavan
Abstract: The aim of this study is to investigate different roof shapes with respect to air flow and indoor temperature in order to find efficient roof shapes for residential buildings in Tehran, Iran. First, an analytical model is defined and then various roof types are modelled. Theoretical modelling is presented to assess the accuracy of the measurement procedures and the uncertainty of experimental modelling. Mathematical and computational field dynamics (CFD) modelling and simulation methods are applied; a κ - ε standard model and finite difference discretisation technique are used to simulate the velocity and pressure path lines as well as the temperature. The results indicate that the energy performance of a domed roof is more efficient compared to flat, vaulted and pitched roofs. In the case of indoor temperature, a domed roof is about 8 K cooler. Also, the wind flow pattern around domed and pitched roofs is more complex; differences in the wind velocity and pressure are noticeable compared to the other roof types. It is concluded that roof geometry and shape has a major influence on reducing heat transfer and balancing roof temperature.